THE EFFECTIVENESS OF ARBITRATION AS AN EXPENSIVE ALTERNATIVE DISPUTE RESOLUTION - Rahmatsyah Rahmatsyah (Faculty of Law, Universitas Pekalongan, 2023)
Arbitration is an alternative non-litigation dispute resolution which has great demand but it has many weaknesses including the high cost of arbitration and decisions that cannot be executed immediately if registration has not been made at the District Court. Thus, the purpose of the analysis are 1) to analyze the juridical value of arbitration when compared to dispute resolution by litigation and 2) to analyze the effectiveness of arbitration as an effort to settle disputes outside of the court system. This study employed a normative legal methodology. The following are the outcomes of this study: Arbitration is a form of alternative dispute resolution that is widely utilized by individuals, individuals and legal entities, between legal entities, etc. in the context of commercial law. Arbitration is widely chosen because dispute resolution is carried out in a closed, flexible and faster way than litigation and has binding legal force. Arbitration has more value, if the process is carried out correctly, observant in analyzing the problems and fulfilling the elements of the rules regarding the execution of the arbitral award. 2) The arbitration will be legally binding if the parties comply with the arbitration rules in the country where the matter will be executed.. Conclusion: arbitration remains an effective non-litigation dispute resolution option but must pay attention to the arbitration process and provisions so that the parties' awareness will arise to register the results of the arbitration decision and comply with the arbitration law applicable in each country.